Steatocystoma multiplex limited to the forearms - Yasser Alqubaisy; Yazeed Alkhalifah (Wolters Kluwer Medknow Publications, 2016)
Steatocystoma multiplex is a rare disorder of the pilosebaceous unit. We reported Thirty-seven years old female presented with small round lumps in her forearms noticed five years back. The cysts size and number did not increase over the past five years with no redness, pain or itching and no family history of a similar condition. The features of steatocystoma multiplex and its dermatological finding are discussed.